ECONOMIC AND CONSTITUTIONAL-LEGAL ASPECTS OF THE PUBLIC ADMINISTRATION OF TERRITORIAL COMMUNITIES UNDER THE CONDITIONS OF MARITAL LAW - Prypkhan , I.I.; Shchur , R.I. (The actual problems of regional economy development, 2023)
The article proves that the effective functioning of territorial communities is possible only under certain prerequisites and conditions, which together form the basis of local self-government. That is, under the foundations of the administrative-territorial reform started in 2014, we understand the opportunities and conditions objectively created in society, the totality of which formed the basis on which the entire system of local self-government development is built, including territorial communities, as the basic link of such a system. The purpose of the article is the need to deepen the relevant scientific research in order to clarify the economic and constitutional and legal aspects of the public management of territorial communities in the conditions of martial law. The main research methods used in the article are the methods of induction, deduction, abstraction, analysis and synthesis. The main feature of the decentralization reform is a new approach to the distribution and implementation of power and other management functions, which involves a departure from the hierarchical system of management and organization of power, a high degree of independence of a number of subjects while reducing the scope of control and supervision of their activities. According to the decentralized model of the organization of power, a higher authority cannot interfere in the activities of a lower authority, cannot carry out administrative activities in relation to it, cannot issue orders or orders. The limits of self-government of bodies performing tasks according to the principles of decentralization of state administration are determined by control measures. The article focuses on the fact that in areas where martial law has been imposed, in order to ensure the effectiveness of the Constitution and laws of Ukraine, the establishment and implementation of measures of the legal regime of martial law, defense, public safety and order together with the bodies of military administration, protection of rights, freedoms and legitimate interests of citizens, the President of Ukraine can create temporary state bodies - military administrations. It was also established that in the conditions of martial law, territorial communities demonstrated effective activity in terms of interaction with state authorities, military organizations, public associations in the implementation and protection of rights, freedoms and ensuring the livelihood of the community population. This became the basis of the successfully implemented administrative and territorial reform and the establishment of new foundations in public administration.